ANALISIS KEPATUHAN WAJIB PAJAK BADAN BERDASARKAN REALISASI PENERIMAAN PAJAK PENGHASILAN PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA CILEGON - Erlina Sari Pohan; Deasy Femayona Devi; Giska Rizki Rofiani (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to examine the Analysis of Compliance with Corporate Taxpayers Based on Realization of Income Tax Receipts at Pratama Tax Service Office (KPP) Cilegon. The research method used in this research is descriptive analysis. With this method, the research data is compiled, interpreted, described and analyzed. The type of data used in this study uses qualitative data, data obtained from KPP Pratama Cilegon from 2014-2017. The results of this study conclude that when viewed from 2014-2017 the number of corporate taxpayers increases every year. The increase in the number of corporate taxpayers above shows that the potential for corporate income tax revenues will increase every year. Target and acceptance of corporate income tax increase. In 2014-2015 tax receipts reached the target set. It's just that in 2016-2017 with a higher target, the realization of corporate income tax revenue does not reach the specified target. Efforts made to optimize income tax receipts at Pratama Tax Service Office (KPP) Cilegon are to carry out socialization, drop box, and pick up the ball.